2021
DOI: 10.1007/s00405-021-06728-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of head and neck cancer patients during COVID-19 pandemic

Abstract: Purpose Impact of COVID-19 pandemic on healthcare is huge. We intended to demonstrate how COVID-19 pandemic affected primary head and neck oncology patient’s referral and admission to a tertiary center by comparing the retrospective patient data in March–September 2020 and the same period in 2019. Methods In this cross-sectional study, from March 15th, 2020 to September 15th, 2020, medical records of 61 patients (Group 1) diagnosed and scheduled for surgery for head and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 9 publications
13
75
3
4
Order By: Relevance
“…This study reports the effects of the COVID-19 pandemic on TNM staging at presentation and treatment choices for patients with newly diagnosed head and neck cancer. There was an odds ratio of 2.141 for having more advanced regional nodal metastatic disease at initial presentation during the pandemic, confirming what has been previously reported in a smaller population [8] . This finding was in the absence of any change in presenting symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study reports the effects of the COVID-19 pandemic on TNM staging at presentation and treatment choices for patients with newly diagnosed head and neck cancer. There was an odds ratio of 2.141 for having more advanced regional nodal metastatic disease at initial presentation during the pandemic, confirming what has been previously reported in a smaller population [8] . This finding was in the absence of any change in presenting symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…For many solid malignancies, treatment delays have been reported and patient encounters for cancer treatment have decreased during the pandemic [4] , [5] , [6] . There have been reports of delays associated with head and neck cancer care [7] , [8] , although there is minimal evidence around how delays impact oncologic care. Patients themselves acknowledge delaying cancer care due to pandemic-related concerns [9] .…”
Section: Introductionmentioning
confidence: 99%
“…5 Indeed, new data from Turkey highlight a prolonged patient delay during the COVID-19 pandemic with a high incidence of T3/T4 head and neck carcinomas and an increased mean time from onset of the first symptoms to hospital admission. 6 In Japan, extended treatment delays have also been reported for patients with lung cancer during the COVID-19 pandemic, 7 while in China, an extended treatment delay for the initiation of radiotherapy in patients with nasopharyngeal carcinoma has been observed. 8 In the context of the ongoing pandemic, other studies have reported a strong impact of COVID-19 on patients with thoracic cancer, resulting in higher mortality and lower intensive care unit admissions.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed no significant differences between group 1 and group 2 regarding tumour size, nodal metastasis and stage. Some Authors [5] , [6] found a significant upstaging of malignancies in the pandemic period. We think that the strategy in use in our department could have prevented this phenomenon.…”
Section: Discussionmentioning
confidence: 99%